Attentional biases and vulnerability to depression. - Ruipérez Rodríguez, Mª Ángeles; Baños Rivera, Rosa Mª; Belloch Fuster, Amparo; Gallardo Pérez, Myriam (The Spanish Journal of Psychology, 1999)
Sin resumen